ANALYSIS THE THEORY OF THE GENRE BY IGOR KACHUROVSKYY IN THE CONTEXT OF CENTURIES OF LITERARY TRADITION - Kubyshkina, C. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article there has been analysed the classification of large, small and medium epic genres was offered by Igor Kachurovskyy. There has been offered analysis of the researcher’s scheme of the epic genres in the light of the Slavic genre typology There has been illuminated the history of the genre.. There has been defined the genre specificity of the short stories. There has been established an approach to the classification of the novel genre.